Matematyka

Autorzy:Wojciech Babiański, Lech Chańko, Joanna Czarnowska

Wydawnictwo:Nowa Era

Rok wydania:2015

Uprość wyrażenie 4.75 gwiazdek na podstawie 8 opinii
  1. Liceum
  2. 1 Klasa
  3. Matematyka

`a)\ (xy^-1)/(x^-2y^-2)=x/x^-2*y^-1/y^-2=x^(1-(-2))*y^(-1-(-2))=x^(1+2)*y^(-1+2)=x^3y` 

`b)\ (xy^-1z^-1)/(x^2y^-2)=x/x^2*y^-1/y_2*z^-1=x^(1-2)*y^(-1-(-2))*z^-1=x^-1*y^(-1+2)*z^-1=x^-1yz^-1` 

`c)\ (2^-1x^4y^-3)/(4^-2x^-4y^-6)=2^-1/4^-2*x^4/x^-4*y^-3/y^-6=2^-1/(2^2)^-2*x^(4-(-4))*y^(-3-(-6))=2^-1/2^-4*x^(4+4)*y^(-3+6)=` 

`\ \ \ =2^(-1-(-4))x^8y^3=2^(-1+4)x^8y^3=2^3x^8y^3=8x^8y^3` 

`d)\ (x^-2z^4)^(-1)*(x/z)^-2=(x^-2)^-1*(z^4)^-1*(z/x)^2=x^2*z^-4*z^2/x^2=` 

`\ \ \ =x^2*1/z^4*z^2/x^2=(strikex^2*z^2)/(z^4*strikex^2)=z^2/z^4=z^(2-4)=z^-2` 

`e)\ (x^4y^2-5y^-3)/(x^4y^-3)=(strikex^4 y^2)/(strikex^4 y^-3)-(5strikey^-3)/(x^4strikey^-3)=y^2/y^-3-5/x^4=y^(2-(-3))-5x^-4=y^(2+3)-5x^-4=y^5-5x^-4` 

`f)\ (x^2-y^2):(x^-1+y^-1)=(x^2-y^2):(1/x+1/y)=(x^2-y^2):(y/(xy)+x/(xy))=` 

`\ \ \ =(x^2-y^2):(y+x)/(xy)=(x^2-y^2)*(xy)/(x+y)=((x^2-y^2)xy)/(x+y)=((x-y)(x+y)xy)/(x+y)=(x-y)xy`